Negative effect of prolonged cecal intubation time on adenoma detection in female patients - Yasuhiko Hamada; Kyosuke Tanaka; Noriyuki Horiki; Junya Tsuboi; Reiko Yamada; Misaki Nakamura; Satoshi Tamaru; Tomomi Yamada; Hayato Nakagawa (JGH Open, 2023)
Abstract Background and Aim Withdrawal time of the colonoscope is associated with adenoma detection. However, the association between cecal intubation time and adenoma detection remains unclear. This study aimed to evaluate the association between cecal intubation time and adenoma detection. Methods This retrospective study analyzed prospectively collected data from a randomized controlled trial on female patients who underwent colonoscopy in an academic hospital. The primary outcome was the mean number of all adenomas detected per patient. Secondary outcomes included the mean number of advanced, diminutive, small/large, right‐sided colonic, and left‐sided colonic adenomas detected per patient. Furthermore, the detection rates of all categories of adenoma were evaluated. Results The analysis included 216 female patients aged ≥20 years. The correlation analysis did not reveal a significant relationship (P = 0.473) between cecal intubation and withdrawal times. The mean number of all adenomas detected per patient declined by approximately 30% (1.05–0.70) from the fastest to the slowest insertion time quartile. Adjusted regression analysis showed a significant decrease in the mean number of all adenomas detected per patient with increased intubation time (relative risk, RR = 0.87; 95% confidence interval, 0.76–0.99, P = 0.045), whereas the mean number of other categories of adenomas detected per patient and the detection rates of all categories of adenoma were not associated with the cecal intubation time. Conclusions This study showed a significant association between prolonged cecal intubation time and decreased adenoma detection. The cecal intubation time may be a significant quality indicator for colonoscopy.